The civil sphere - Alexander, Jeffrey C., 1947- (New York ; Oxford : Oxford University Press, 2006)
Societies are not governed only by power and self-interest. What then does make societies function? How do real individuals live together in real societies in the real world? This work addresses this central paradox of modern life.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Civil society; Cultural pluralism; Social interaction